Polymeric Coating Applied for Corrosion Protection of Mild Steel in Corrosive Medium - Rajesh Kumar Singh; Rizwana Khatoon (International Journal of Advance in Molecular Engineering, 2025)
Mild steel is coated with a polymer layer of polybutadiene for protection. However, this coating does not effectively safeguard the metal in environments containing moisture, sulphur dioxide, or chloride. These pollutants interact with the polybutadiene-coated surface, creating a highly corrosive atmosphere. Moisture condenses on the coated metal surface and absorbs sulphur dioxide, forming sulphuric acid. This acid initiates both chemical and electrochemical reactions with the polymer-coated metal, accelerating the corrosion process Chloride ions penetrate the coating through osmosis or diffusion, forming corrosion cells on the metal surface. Oxygen depletion inside and outside the coating further promotes corrosion cell formation. As a result, these pollutants cause both internal and external corrosion by breaking the internal bonds within the polybutadiene layer and weakening adhesion between the coating and the metal substrate. Consequently, the metal exhibits several types of corrosion, including galvanic, pitting, stress, crevice, blistering, and embrittlement To mitigate corrosion in such aggressive environments, nanocoating and filler techniques are employed. Octahydrodibenzo annulene-5,12-dihydrazone is used as the nanocoating material, while magnesium sulfide (MgS) serves as the filler. The corrosion rate of the polymer-coated mild steel is determined using gravimetric methods, while corrosion potential, current, and current density are measured with a potentiostat. Nanocoating is applied using a nozzle spray technique The adsorption behavior of the coating is analyzed using the Langmuir isotherm and Arrhenius equation. Surface deposition and bond formation of the nanocoating and filler materials are evaluated through parameters such as activation energy, heat of adsorption, free energy, enthalpy, and entropy. Experimental findings on surface coverage and coating efficiency reveal that the nanocoating and filler materials form a composite thin-film barrier on the polybutadiene-coated mild steel surface, significantly enhancing its corrosion resistance.
Keywords: Filler; Pollutants; Polybutadiene-coated mild steel; composite thin film barrier; nanocoating